Connectomics in Brain Aging and Dementia – The Background and Design of a Study of a Connectome Related to Human Disease - Cohen, Ann D.; Bruña, Ricardo; Chang, Yue-Fang; Cheng, Yu; Doman, Jack; Huppert, Ted; Kim, Tae; Maestu, Fernando; Roush, Rebecca E.; Snitz, Beth E.; Becker, James T. (Frontiers in Aging Neuroscience, 2021)
The organizing principle of our research project is the idea that the expression of cognitive dysfunction in the elderly is the result of two independent processes — the neuropathology associated with AD, and second the neuropathological changes of cerebrovascular disease. Synaptic loss, senile plaques, and neurofibrillary tangles are the functional and diagnostic hallmarks of AD, but it is the structural changes as a consequence of vascular disease that reduce brain reserve and compensation, resulting in an earlier expression of the clinical DAT syndrome. This work is being completed under the auspices of the Human Connectome Project (HCP). We have achieved an equal representation of Black individuals (vs. Whites individuals) and enrolled 60% Women. Each of the participants contributes demographic, behavioral and laboratory data. We acquire data relative to vascular risk, and the participants also undergo in vivo amyloid imaging, and magnetoencephalography (MEG). All of the data are publicly available under the HCP guidelines using the Connectome Coordinating Facility and the NIMH Data Archive. Locally, we use these data to address specific questions related to structure, function, AD, aging and vascular disease in multi-modality studies leveraging the differential advantages of MRI, fMRI, MEG, and in vivo Aβ imaging.